2022
DOI: 10.3389/fphys.2022.1065278
|View full text |Cite
|
Sign up to set email alerts
|

Moderate exercise protects against joint disease in a murine model of osteoarthritis

Abstract: Exercise is recommended as a non-pharmacological therapy for osteoarthritis (OA). Various exercise regimes, with differing intensities and duration, have been used in a range of OA rodent models. These studies show gentle or moderate exercise reduces the severity of OA parameters while high intensity load bearing exercise is detrimental. However, these studies were largely conducted in rats or in mouse models induced by severe injury, age or obesity, whilst destabilization of the medial meniscus (DMM) in mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Studies like these are important as they highlight the molecular differences between various factors that influence OA progression. Considering studies have shown that exercise can induce knee OA [29][30][31], and paradoxically, studies also show exercise reduces OA development [25,32] in mice, it would be imperative to elucidate the genetic factors, and also the exercise parameters that elicit these contrasting results. Here we implemented a modified forced treadmill running protocol previously reported to induce knee OA in mice [14].…”
Section: Discussionmentioning
confidence: 99%
“…Studies like these are important as they highlight the molecular differences between various factors that influence OA progression. Considering studies have shown that exercise can induce knee OA [29][30][31], and paradoxically, studies also show exercise reduces OA development [25,32] in mice, it would be imperative to elucidate the genetic factors, and also the exercise parameters that elicit these contrasting results. Here we implemented a modified forced treadmill running protocol previously reported to induce knee OA in mice [14].…”
Section: Discussionmentioning
confidence: 99%
“…38 Bomer et al, 22 37 Studies like these are important as they highlight the molecular differences between various factors that influence OA progression. Considering studies have shown that forced treadmill running can induce knee OA, [39][40][41] and, paradoxically, also forced treadmill running can reduces OA development in mice, 35,42 it would be imperative to elucidate the genetic factors alongside the exercise parameters that elicit these contrasting results.…”
Section: Forced Treadmill Running Caused Accelerated Ivd Degeneration...mentioning
confidence: 99%
“…To elicit OA in rats, subchondral bone and cartilage changes can be induced by instability surgery, with varying levels of severity ( Bendele, 2001 ; Hayami et al, 2006 ; Lampropoulou-Adamidou et al, 2014 ; McCoy, 2015 ; Kuyinu et al, 2016 ). The intensity of changes is influenced by several factors, including the duration and the degree of joint loading affected by activity ( Iijima et al, 2015 ; Huesa et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%